Association of Silent Cerebrovascular Disease Identified Using Natural Language Processing and Future Ischemic Stroke. (28th September 2021) - Kent, David M.; Leung, Lester Y.; Zhou, Yichen; Luetmer, Patrick H.; Kallmes, David F.; Nelson, Jason; Fu, Sunyang; Zheng, Chengyi; Liu, Hongfang; Chen, Wansu
Abstract : Background and Objectives: Silent cerebrovascular disease (SCD), comprising silent brain infarction (SBI) and white matter disease (WMD), is commonly found incidentally on neuroimaging scans obtained in routine clinical care. Their prognostic significance is not known. We aimed to estimate the incidence of and risk increase in future stroke in patients with incidentally discovered SCD. Methods: Patients in the Kaiser Permanente Southern California (KPSC) health system aged ≥50 years, without prior ischemic stroke, transient ischemic attack (TIA), or dementia/Alzheimer disease receiving a head CT or MRI between 2009 and 2019 were included. SBI and WMD were identified by natural language processing (NLP) from the neuroimage report. Results: Among 262, 875 individuals receiving neuroimaging, NLP identified 13, 154 (5.0%) with SBI and 78, 330 (29.8%) with WMD. The incidence of future stroke was 32.5 (95% confidence interval [CI] 31.1, 33.9) per 1, 000 patient-years for patients with SBI: 19.3 (95% CI 18.9, 19.8) for patients with WMD and 6.8 (95% CI 6.7, 7.0) for patients without SCD. The crude hazard ratio (HR) associated with SBI was 3.40 (95% CI 3.25 to 3.56) and for WMD 2.63 (95% CI 2.54 to 2.71). With MRI-discovered SBI, the adjusted HR was 2.95 (95% CI 2.53 to 3.44) for those <65 years of age and 2.15 (95% CI 1.91 to 2.41) for those ≥65. With CT scan, the adjusted HR was 2.48 (95% CI 2.19 to 2.81) for those <65 and 1.81 (95% CI 1.71 to 1.91) for those ≥65. The adjusted HR associated with a finding of WMD was 1.76 (95% CI 1.69 to 1.82) and was not modified by age or imaging modality. Discussion: Incidentally discovered SBI and WMD are common and associated with increased risk of subsequent symptomatic stroke, representing an important opportunity for stroke prevention.